Clinical screening of oropharyngeal dysphagia: standard of care - Caviedes, Iván; Herth, Felix (The European respiratory journal, 2017)
Tweetable abstract ERSpublications click to tweetThe three-ounce water test is a well-known and useful bedside screening tool for oropharyngeal dysphagia http://ow.ly/9Krl30cW2HJ
Gesehen am 04.05.2018